Analysis of the Strategic Planning Process in a Colombian Banking Institution - Giraldo Gómez, Julián David; García-Muñoz Aparicio, Cecilia (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To demonstrate how the corporate strategy of the banking institution is related to the market and its stakeholders in order to obtain an academic vision. MATERIAL AND METHOD: The research design is of a descriptive and documentary exploratory type, due to the fact that the collection of information was done through secondary sources such as official documents and scientific articles to observe the operation of Banco de Occidente, one of the most important financial institutions in Colombia formed by investors and a wide range of financial products and services. This company has developed different types of interesting strategic planning during its trajectory, in order to be current in the market according to the changes of the environment, and carrying out permanent technological surveillance. RESULTS: An analysis of strategic guidelines was carried out, showing the way in which the institution carries out financial planning. CONCLUSIONS: The position of the object of study towards the environment, social and economic aspects involving stakeholders is demonstrated.